1988
DOI: 10.1038/bjc.1988.246
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic factors for survival in stage IIIB and IV Hodgkin's disease: a multivariate analysis comparing two specialist treatment centres

Abstract: A multivariate analysis of prognostic factors was carried out on 301 patients with clinical or pathological stage III/IV Hodgkin's disease treated using the same combination chemotherapy (MVPP) at two centres (Christie Hospital, Manchester, 151 patients, St. Bartholomew's Hospital, London, 150 patients). There were no significant difference in CR or relapse free and overall survival at 5 and 10 years between the two groups. Cox analysis of the Christie data alone produced four significant factors for survival … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

1991
1991
2014
2014

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(18 citation statements)
references
References 17 publications
0
18
0
Order By: Relevance
“…Overall survival rates at 2 years in the low-, intermediate-and high-risk groups were 100%, 93%, and 71% respectively (log-rank test P < 0.01) (Figure 2). Using our data set, we evaluated the importance of the TNF ligand receptor-based prognostic index along with five other reported prognostic indices for HD (Wagstaff et al, 1988;Straus et al, 1990;Proctor et al, 1991;Hasenclever et al, 1995;Lee et al, 1997). The TNF ligand receptor-based prognostic index was the only index to have a significant prognostic impact for FFP survival ( Figure 3K).…”
Section: Plasma Cytokine and Receptor Levels And Patient Outcomementioning
confidence: 99%
See 1 more Smart Citation
“…Overall survival rates at 2 years in the low-, intermediate-and high-risk groups were 100%, 93%, and 71% respectively (log-rank test P < 0.01) (Figure 2). Using our data set, we evaluated the importance of the TNF ligand receptor-based prognostic index along with five other reported prognostic indices for HD (Wagstaff et al, 1988;Straus et al, 1990;Proctor et al, 1991;Hasenclever et al, 1995;Lee et al, 1997). The TNF ligand receptor-based prognostic index was the only index to have a significant prognostic impact for FFP survival ( Figure 3K).…”
Section: Plasma Cytokine and Receptor Levels And Patient Outcomementioning
confidence: 99%
“…The most common factors that have been found to be associated with an unfavourable outcome include advanced stage, presence of extranodal disease and bulky tumour, mixed cellularity or lymphocyte depletion histology, age above 45 years, presence of B symptoms, male gender, elevated serum levels of LDH, P2-microglobulin, alkaline phosphatase and low serum albumin levels. However, despite the presence of several prognostic indices for HD, there is no agreement on the definition of sufficiently high-risk groups of patients for whom the prognosis is especially poor and for whom up-front high-dose therapy should be advised (Wagstaff et al, 1988;Straus et al, 1990; Proctor et al, 1991;Hasenclever et al, 1995;Lee et al, 1997). Thus, the search for more discriminating prognostic factors identifying vulnerable patients with a high risk of resistance or relapse is still an open challenge.…”
mentioning
confidence: 99%
“…Wagstaff et al (1988), analysing 300 patients with advanced Hodgkin's disease, found that male patients with stage IV disease and (aged greater than 45 years and/or lymphocytopenia) had the worst prognosis, with a survival of 34% at 5 years. Proctor et al (1991) developed a prognostic index based on disease stage, age, haemoglobin and absolute lymphocyte count to predict patients who were likely to die of progressive disease.…”
Section: Discussionmentioning
confidence: 99%
“…Four other reported prognostic indices (Wagstaff et al, 1988;Straus et al, 1990;Proctor et al, 1991;Hasenclever et al, 1995) were evaluated using our data set. The performance of these indices was analysed separately for the 6-to 18-month period and the whole of the follow-up period.…”
Section: Comparison Of Data With Other Reported Prognostic Indicesmentioning
confidence: 99%
“…When this strategy was planned in Nantes in the 1980s, three risk factors were selected, based on available studies: CS IV at diagnosis, MM у0.45 at diagnosis, and incomplete response to the first-line chemotherapy. CS IV is a well-known unfavorable factor that was identified more particularly in four studies reporting on prognostic scores, which included a large number of patients (Hasenclever and Diehl, 17 Wagstaff et al, 18 Proctor et al, 19 and Gobbi et al 20 ). The second poor prognostic factor is MM у0.45 at diagnosis, that we chose as an indicator of tumor burden.…”
Section: Discussionmentioning
confidence: 99%